PERTIMBANGAN HAKIM MILTER DALAM MEMUTUS PENYALAHGUNAAN NARKOTIKA YANG DILAKUKAN TENTARA NASIONAL INDONESIA - Putri, Novitaningrum Eka; Kristiyadi, Kristiyadi (Verstek, 2023)
This research aims to know determine the legal authority of the Military Court in hearing cases of Narcotics Abuse by the TNI and to know the legal considerations of the Military Court in the process of Imposing a Criminal Decision on Narcotics Abuse for members of the TNI. This research is a normative legal research that is prescriptive and applied with case studies. The technique of collecting primary and secondary legal materials used is the study of documents or library materials. The results of this study are narcotics crimes in the scope of general and military courts based on Law No. 22 of 1997concerning narcotics (crimes are general crimes, in relation to perpetrators who are members of the military, settlements are based on regulations that apply among members of the military). The judge's consideration factor in sentencing the perpetrators of narcotics crimes among members of the military is more directed to good services and achievements while carrying out military duties. The burden of punishment for members of the military who commit criminal acts(violating military discipline) is the existence of additional punishments, which are military in nature.Keywords: Narcotics, TNI, Military Court, Judge's Consideration